2008
DOI: 10.3171/ped/2008/1/3/187
|View full text |Cite
|
Sign up to set email alerts
|

Craniospinal Langerhans cell histiocytosis in children: 30 years' experience at a single institution

Abstract: Object The goal of this study was to review a large series of patients with Langerhans cell histiocytosis (LCH) who had craniospinal lesions to assess the long-term course, outcome, and efficacy of treatment of the disease. Methods Forty-four patients with LCH who presented to a single pediatric neurosurgical department between 1976 and 2006 were retrospectively reviewed. <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 57 publications
(86 reference statements)
1
15
0
2
Order By: Relevance
“…[6] The incidence of LCH in children is 1 to 5 children per million per year. [7] LCH almost affects any organ in the form of unifocal or multifocal lesions. [3] In children, bone is the most common single organ and the skull is the most affected site.…”
Section: Discussionmentioning
confidence: 99%
“…[6] The incidence of LCH in children is 1 to 5 children per million per year. [7] LCH almost affects any organ in the form of unifocal or multifocal lesions. [3] In children, bone is the most common single organ and the skull is the most affected site.…”
Section: Discussionmentioning
confidence: 99%
“…In the multicenter Depression Network Study, investigators diagnosed postpartum major depressive disorder in 42% of 31 women with a sister who had experienced major depressive disorder after delivery compared with only 15% of 59 women whose sisters had not experienced postpartum major depressive disorder. 60 A report from the Genetics of Recurrent Early-Onset major depressive disorder study revealed that having a sibling with major depressive disorder during pregnancy or after delivery increased the odds of a similar episode in the other sibling by 2.28 (95% CI 1.13-4.58); a sibling with postpartum major depressive disorder increased the odds of having postpartum major depressive disorder by 4.96 (95% CI 1.51-10.42). 61…”
Section: Familial Aggregationmentioning
confidence: 96%
“…Another report describing how JLSG-02 compares to JLSG-96 in terms of the therapeutic results of the entire cohort (and with longer follow-up times) is currently being prepared as a separate paper. Our recent literature survey has shown that of the studies discussing the management of bone LCH, most mix patients with single bone (monostotic) disease with patients with multiple bone (polyostotic) disease [10][11][12][13]; many also do not separate the pediatric patients from the adult patients [4,5]. Thus, the bone involvement of pediatric cases with SMFBand MSB-type LCH has not been analyzed systematically.…”
Section: Discussionmentioning
confidence: 98%